Hepatitis C Virus RNA Transcript Associates with Prognosis in Non‐human Papillomavirus Associated Head and Neck Squamous Cell Carcinoma. (16th February 2021) - Tang, Bin; Zhu, Gangcai; Chen, Changhan; Zheng, Siyuan; Pu, Yuting; Xu, Yimin; Huang, Huimei; Wang, Gang; Huang, Donghai; Liu, Yong; Zhang, Xin
Abstract : Objective/Hypothesis: Hepatitis C virus (HCV) was reported to associate with head and neck squamous cell carcinoma (HNSCC) in many studies. However, its correlation with prognosis of non‐human papillomavirus (HPV) associated HNSCC remains unknown. Here, we sought to investigate clinical significance of HCV RNA transcript in non‐HPV associated HNSCC by analyzing corresponding RNA‐seq data. Study Design: A retrospective cohort study. Methods: Four hundred and forty‐eight non‐HPV associated HNSCC patients with aligned RNA‐seq and clinical follow‐up data were included and divided into two groups: low‐HCV and high‐HCV. Means of continuous variables and proportions of categorical variables were compared using independent sample t ‐test and chi‐square test, respectively. Survival data were compared using Cox regression analysis, Kaplan–Meier curves, and log‐rank test. Expression of genome‐wide mRNAs and abundance of immune cells were compared using volcano plot and cell signature estimated score analysis. Results: HCV RNA transcript negatively correlates with pathologic ( P  = .028) and clinical‐stage ( P  = .023), clinical N stage ( P  = .025), and nodal extracapsular spread ( P  = .042) and is an independent prognosis factor in non‐HPV associated HNSCC (HR = 1.488; 95% CI: 1.004–2.206; P  = .048). Elevated expression of HCV improved 5‐year overall survival (43.6% vs. 53.2%; P  = .035) in all non‐HPV associated HNSCC patients, the same as in male (46.6% vs. 58.7%; P  = .049), clinical M0 stage (42.8% vs. 52.9%; P  = .036), white (42.9% vs. 55.9%; P  = .010), and histologic grade 1 to 2 subgroups (42.1% vs. 57.2%; P  = .043). The expression of several immune‐related genes and abundance of some immune cells significantly changed with the increase of HCV RNA transcript, while HCV‐related oncogenes and tumor suppressor gene did not. Conclusions: HCV RNA transcript is an independent favorable factor for prognosis of non‐HPV associated HNSCC. Levels of Evidence: 4 Laryngoscope, 131:1774–1781, 2021